SURVEILANS VEKTOR MALARIA DI DESA ANEKA MARGA, KECAMATAN ROROWATU UTARA, KABUPATEN BOMBANA, PROVINSI SULAWESI TENGGARA - Sunaryo Sunaryo (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2010)
One of the intensification of malaria control programs in South East Sulawesi is vector surveyllance in the form of entomological survey. The aimed of this survey was to provide data and information on malaria vector usefull for vector control activity. Vector Surveyllance activity had been done to know vector fluctuation data, vector behaviour, type of breeding places in order to know the peak of vector density. Peak of vector density is usefull for malaria awareness in different type of ecology. Survey had been done in October 2010 in Aneka Marga village, Rorowatu Utara sub district, Bombana District, South East Sulawesi Province. Survey had been done during 4 night serially, start from 18.00 pm to 06.00 am with 6 mosquito collector, 3 collectors catching mosquitoes out door, 3 collectors catching mousquitoes in door for 45 minutes. 15 minutes out doors catching the mosquitoes that rest in cage, while indoors catching the mosquitoes that rest on house wall. It was found that Anopheles subpictus was the dominant vector with Man Biting Rate(MBR) in door was 0,28/man/hours and MBR out door was 0,64/man/hours. Peak of An. subpictus bites at 23.00 pm, the breeding places of An. subpictus in fish bowl, around 1 km from settlement. The density of Anopheline larvae was 3 larva/deeper.